La problemática de la conservación de los trópicos húmedos americanos - Rubio Recio, José Manuel (Geographicalia, 2017)
This article constitutes a reflection about the multiple problems derived from the conservation in the countries of the American humid tropics. We understand by conservation the management that has to be done in an espace in order to use its natural potentials, allowing its regeneration to avoid losses or imbalances. The conservation-models exported from our temperate worl dare not applicabkle there; either the dimensions of the ecosystems to preserve, nor the socioeconomic situation of the people who own them, incomparable to ours.